STUDY OF TIN POWDER SYNTHESIS USING CONSTANT CURRENT ELECTROLYSIS METHOD - Perdana, Deviana
The advances of technology that lead to miniaturization of electronic circuits cause an increase in demand of solder paste in the world. It becomes a special opportunity for Indonesia because at the moment Indonesia is the second largest tin producing country in the world. The production of tin powder using electrolysis method has several advantages compared to the atomization method, for instances, it can produce nano powder particles, requires relatively simple equipment, and able to produce high purity powder. Tin powder as a main constituent of solder paste should have spherical or nearly spherical morphology. The morphology and grain size of the powder obtained from the electrolysis method is influenced by the conditions of the electrolysis process. In this research, the effect of constant current electrolysis variables on the particle size and powder’s morphology is studied. This electrolysis experiment consisted of two stages. The first step was carried out to determine the optimum parameters using the Taguchi experimental design. Then, the second stage was carried out by varying the optimum parameters obtained from the first stage’s experimental result to find out the effect of Sn2+ concentration, mass ratio of thiourea: gelatine as additives, current density, and electrolysis time on the morphology of the deposit and current efficiency. Electrolyte solution was prepared by dissolving 48.4 ml of 17.8 M H2SO4 in distilled water to obtain 850 ml of H2SO4 with 1.02 M concentration. Electrolysis experiments were carried out using constant current source, pure tin anode, and titanium cathode. After the electrolysis experiment was completed, the tin powder deposits were analyzed by Scanning Electron Microscope (SEM), Particle Size Analyzer (PSA), and X-ray Diffraction (XRD) to determine the morphology, grain size, and composition of element and compound within the powder deposit. The optimum condition was achieved at Sn2+ concentration of 1,66 gpl, mass ratio of thiourea:gelatine 1:4, current density 1 A/dm2, and electrolysis time 10 minutes. The current efficiency increases with increasing Sn2+ concentration, decreasing current density, and shorter electrolysis time. Irregular grain morphology was obtained when the Sn2+ concentration higher than 4,96 gpl. As the concentration of gelatin increased within varied value, the morphology of the particles tends to change into cubical or nearly spherical. Needle-like morphology was obtained at current density higher than 2A/dm2. Meanwhile, as the electrolysis time exceeds 60 minutes, the obtained deposit was not in the form of powder but in form of a compact plate.